Clonal Dissemination of Plasmid-Mediated Carbapenem and Colistin Resistance in Refugees Living in Overcrowded Camps in North Lebanon - Adel Azour; Charbel Al-Bayssari; Tania Nawfal Dagher; Faraj Fajloun; Mark Fajloun; Jean-Marc Rolain (MDPI AG, 2021)
Carbapenem and colistin-resistant bacteria represent a global public health problem. Refugees carrying these bacteria and living in inadequate shelters can spread these microorganisms. The aim of this study was to investigate the intestinal carriage of these bacteria in Syrian refugees in Lebanon. Between June and July 2019, 250 rectal swabs were collected from two refugee camps in North Lebanon. Swabs were cultured on different selective media. Antibiotic susceptibility testing was performed using the disk diffusion method. Carbapenemase-encoding genes and mcr genes were investigated using real-time polymerase chain reaction (RT-PCR) and standard polymerase chain reaction (PCR). Epidemiological relatedness was studied using multilocus sequence typing (MLST). From 250 rectal swabs, 16 carbapenem-resistant, 5 colistin-resistant, and 4 colistin and carbapenem-resistant Enterobacteriaceae were isolated. The isolates exhibited multidrug-resistant phenotypes. Seven Klebsiella pneumoniae isolates harboured the blaOXA-48 gene, and in addition four K. pneumoniae had mutations in the two component systems pmrA/pmrB, phoP/phoQ and co-harboured the blaNDM-1 gene. Moreover, the blaNDM-1 gene was detected in six Escherichia coli and three Enterobacter cloacae isolates. The remaining five E. coli isolates harboured the mcr-1 gene. MLST results showed several sequence types, with a remarkable clonal dissemination. An urgent strategy needs to be adopted in order to avoid the spread of such resistance in highly crowded underserved communities.